The Beaver Hills Country: A History of Land and Life - Graham A. MacDonald (Athabasca University Press, 2009)
This book explores a relatively small but interesting and unusual region of Alberta between the North Saskatchewan and the Battle Rivers. The Beaver Hills arose where mountain glaciers from the west met continental ice-sheets from the east. An overview of the hills geography helps us to see the complexity and diversity of landscapes, soil types, and vegetation communities. MacDonald relates how climatic cycles, water availability, wildlife, vegetation, and fire have shaped the possibilities and provided the challenges to those who have called the region home or used its resources: Indigenous people, Métis, and European immigrants.
English
Keywords: Alberta history; prairie ecology